A New Computational Model to Predict Breakdown Pressures in Cased and Perforated Wells in Unconventional Reservoirs. Issue 1 (1st December 2018) - Kurdi, Mohammed; Roshan, Hamid
Abstract : Unconventional shale reservoirs are characterised by their extreme low permeabilities and their high in-situ stresses. Multi-stage hydraulic fracturing therefore plays a key role in developing such reservoirs. However, depending on the in-situ stress magnitude and/or regime, breakdown pressures can be too extreme to achieve, given the available surface horsepower capabilities. The local principal stresses surrounding perforation tunnels dictate the required breakdown pressure to induce enough stress to exceed the rock tensile strength. This paper presents a newly developed model to predict the breakdown pressures in cased and perforated wells. Given an arbitrary azimuth and inclination of the wellbore and the in-situ stress magnitude/regime, the model calculates the local stresses around the perforations and consequently predicts the perforations' breakdown pressure and the initial fracture plane orientation. The results from the model indicate as to which perforation initiates first, creating a mini-fracture that extends to create a dominant fracture. This dominant fracture would be the only fracture extending, due to the induced stress shadowing on other mini-fractures and increasing the respective in-situ principal stresses. The model also aids cluster and well placement for highly deviated wells to better identify sweet spots where breakdown pressures are minimal, resulting in maximum hydrocarbon accumulations possible. If the perforations clusters are placed in zones with extreme local principal stresses, the near wellbore fracture widths would be too small to admit any proppant, leading to early proppant screenout. The results from the model shows a critical perforation phasing angle that should be avoided, as the local principal stresses maximise, increasing breakdown pressures. The model aims to advance the current understanding of fracture initiation in highly deviated wells in shale reservoirs. It can also assist engineers to better select sweet spots for well and cluster placement to avoid excessive breakdown pressures and/or potential early proppant screenout.